Building Sípnuuk: A Digital Library, Archives, and Museum for Indigenous Peoples. Issue 3 (2nd October 2017) - Karuk Tribe,; Hillman, Lisa; Hillman, Leaf; Harling, Adrienne R. S.; Talley, Bari; McLaughlin, Angela
ABSTRACT: The tribal codes and laws managing the traditional knowledge system of the Karuk people have been passed on to us by the ikxaréeyav, or Spirit People. Regulated through access restrictions and protocols, we have been able to preserve information about all aspects of Karuk life for thousands of years. Yet over the past 160 years, this system has remained unacknowledged by the legal frameworks of Euro-America. Since 2012, however, the Karuk Tribe has been developing the Sípnuuk Digital Library, Archives, and Museum, providing self-representative and culturally appropriate access to, control over, and preservation of Karuk cultural heritage.